Divided by vaccination? Evaluating the intergroup conflict between pro- and anti-vaccination groups in the post-pandemic era - Maximilian Filsinger; Markus Freitag (Humanities & Social Sciences Communications)
Abstract The vaccination against COVID-19 has torn societies apart. Against this background we evaluate three interrelated research questions: (1) does vaccination polarize citizens even after the COVID-19 pandemic has faded; (2) do opinions about vaccination correlate with group formation and identification, and (3) do we observe opinion-based affective polarization regarding vaccination in the post-pandemic era? Based on two original surveys from Switzerland in early 2022 and late 2023, our results highlight that respondents have distinct opinions about vaccination, but that only pro-vaccination respondents have formed an opinion identity. We also observe an asymmetric affective polarization: pro-vaccination respondents show higher levels of liking toward other pro-vaccination respondents but significant dislike toward anti-vaccination respondents, while the same does not hold true for anti-vaccination respondents. Overall, affective polarization toward vaccination is less pronounced in the aftermath of the health crisis than during the COVID-19 pandemic. However, at a time when globalization is boosting the threat of pandemics, caution is warranted, as an increasing salience of vaccination could widen the divide again.